Pharmacokinetic Evaluation Of Tacrolimus Extended-Release Tablets In Rabbit Experimental Model (Journal of Pharmaceutical Negative Results, 2022)
In this experiment, we compared the pharmacokinetic properties of extended-release tacrolimus tablets to those of a standard medication (Envarsus XR 4 mg). Four healthy rabbits participated in a double-blind, randomised controlled trial. A single dose of 4 mg of each formulation was given to all of the rabbits. There were multiple time points where blood samples were taken (0.5, 1, 2, 3, 4, 5, 6, 8, 10, 12, 14, 16, 20, 24, 36 and 48 hr). AUC 0-t, AUC 0-∞, and Cmax were the pharmacokinetics parameters computed for the formulations. These bioequivalence criteria are met by the test formulation. The study found that the pharmacokinetic profile of Tacrolimus extended-release tablets was favourable. Comparing the reference and test groups, Tacrolimus AUC0-t and AUC0-∞ were found to be 10973.5 and 10892.2 ng/L×h, respectively. t1/2 and Tmax were 8.5 h and 4.21 h, respectively for tacrolimus extended-release tablets. However, CLz/F and Cmax were 875.1 L/h/kg and 775.8 ng/L, respectively. After testing the drug at a dose of 2000 mg/kg for acute oral toxicity, the drug was found non-toxic. Even with the administration of the drug, no major changes were observed in the aforementioned behavioral, biochemical, or haematological markers. Maximum blood concentration, area under the curve, and half-life values in rabbits were not significantly different between the tacrolimus extended-release tablets and the commercially available Envarsus XR. Consequently, it is anticipated that the produced tablets will be bioequivalent to the commercial medicine, allowing for a once-daily dosage regimen in patients with allogenic rejection. This study suggests that extended-release tablets of tacrolimus may be a viable replacement for the currently used medicine in the role of immune-suppressant.